Evaluation of the accuracy of Demirjian method in estimating chronologic ages of 5-17 year-old children and adolescents in Kerman - Mahnaz Sheikhi; Sajad Ghorbanizadeh; Amin Ghasemzadeh; Mehdi Baghestani (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Age estimation plays a critical role in pediatric endocrinology, orthodontics, pediatric dentistry, archaeology, etc. The aim of this study was to evaluate the accuracy of dental age estimation in 5‒17 year-old children and adolescents in Kerman using Demirjian method.Materials and Methods: This retrospective cross-sectional study was carried out on 350 panoramic radiographs of 224 girls and 126 boys, referring to Kerman dental clinics. Simple sampling method was used. Based on Demirjian method two dental radiologists calculated the dental maturity score (DMS) by assessing the seven left mandibular teeth and estimated the dental age for each case. The chronologic age of each patient was obtained from demographic data. Finally, the correlation between estimated dental age and chronologic age was determined by Pearson's correlation coefficient and paired t-test using SPSS statistical software (α = 0.05). Result: Mean dental age in all the subjects was estimated 0.11 year less than the chronologic age. Pearson's correlation coefficient between estimated and chronological ages was 0.95, indicating statistical significance (p value < 0.001). In addition, there was no significant difference between estimated and chronological ages (p value = 0.15). Discussion: Based on the results of the present study, Demirjian method is sufficiently accurate to estimate dental age of children in Kerman is and can be used acceptably. Key words: Age, Dental age, Dental calcification.test